Cross-genomic analysis of human disease genes - Bier, Ethan (Henry Stewart Talks, 2008)
Systematic cross genomic comparison revealed that 75% of human disease genes have clear homologs in Drosophila and that ≈ 30% are highly conserved sequences, The fly is an excellent model multicellular organism for examining the mechanistic function of conserved human disease genes involved in developmental or tissue-related processes, Normal or mutant human disease genes can be mis-expressed in the fly in localized patterns or at specific times using the GAL4-UAS mis-expression system, Flies were used to identify candidate target proteins that are regulated by Ube3a and may contribute to Angelman syndrome, Flies were used to examine the function and interaction of two toxins, Lethal Factor (LF) and Edema Factor (EF), that are produced by Bacillus anthracis, LF cleaves at least two of the four Drosophila MAPKKs and inhibits the function of a third, EF inhibits PKA dependent Hedgehog signaling in the fly wing
Reviewed at 2017/09/25